(untitled) (Historia, 2021)
Here, we tell the story of early postcolonial Botswana’s struggles to refine its citizenship model in the midst of a hostile political environment between the 1960s and 1980s. While being one of the “most peaceful” countries in the region at the time, and in order to stem the tide of militant immigrants, the majority of whom were men, Botswana opted to narrow its citizenship model. Many refugees and exiles were denied citizenship because their “radical masculinities” appeared to present a threat to the existing peace in the country. The article deals with the important question of how Botswana’s historically rooted, patriarchal gender regime influenced the country’s refashioning of its citizenship model against the backdrop of the influx of exiles and refugees of wars of independence. We draw largely from existing scholarship on Botswana’s role in the liberation struggle. In addition, the extant refugees archive, letters to the editor of the Kutlwano magazine, Seretse Khama’s speeches and the Botswana Citizenship Act of 1982/1984 provide primary accounts of how the government and the public attempted to develop and achieve a peaceful, anti-radical national identity during this tumultuous period. Hier vertel ons die verhaal van post-koloniale Botswana se vroeë jare, en bepaal die uitdagings wat betref sy burgerskapmodel te midde van die vyandige politieke klimaat wat die 1960’s tot 1980’s gekenmerk het. Alhoewel Botswana in dié tyd een van die mees "vreedsame” lande in die streek was, het hy te kampe gehad met ’n vloedgolf militante immigrante, waarvan die meerderheid mans was. Botswana het daarom gekies om sy burgerskapmodel te vernou. Vele vlugtelinge en uitgewekenes is burgerskap geweier omdat hulle “radikale manlikheid” as ’n bedreiging vir die heersende vrede in die land beskou is. Hierdie artikel stel belangrike vrae oor Botswana se histories-gewortelde patriargale geslags regime, en die invloed daarvan op die land se hervorming van sy burgerskapmodel, aan die hand van die instroming van uitgewekenes en vlugtelinge van vryheidsoorloë. Ons beroep ons op gevestigde navorsing oor Botswana se rol in die vryheidstryd. Verder verskaf die bestaande vlugtelinge-argief, briewe aan die redakteur van die Kutlwano tydskrif, Seretse Khama se toesprake en die Botswana Burgerskap Wet van 1982/1984, primêre verslae oor die regering en die publiek se pogings om ’n vreedsame, anti-radikale nasionale identiteit tydens dié ontstuimige tydperk te ontwikkel.